2012
DOI: 10.1016/j.taap.2012.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies reveal multiple forms of expression of human microsomal epoxide hydrolase

Abstract: In a previous study, we developed five kinds of monoclonal antibodies against different portions of human mEH: three, anti-N-terminal; one, anti-C-terminal; one, anti-conformational epitope. Using them, we stained the intact and the permeabilized human cells of various kinds and performed flow cytometric analysis. Primary hepatocytes and peripheral blood mononuclear cells (PBMC) showed remarkable differences. On the surface, hepatocytes exhibited 4 out of 5 epitopes whereas PBMC did not show any of the epitope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…EPHX1 may participate in an important pathway in these physiological and pathological processes by providing free AA. Interestingly, a recent study demonstrated multiple forms of expression of EPHX1, and the results implicated the multiple roles of EPHX1 in various cells ( 41 ). In the current study, an EPHX1 form(s) responsible for 2-AG hydrolysis was not characterized, and this possibility deserves future detailed investigation.…”
Section: Downloaded Frommentioning
confidence: 67%
“…EPHX1 may participate in an important pathway in these physiological and pathological processes by providing free AA. Interestingly, a recent study demonstrated multiple forms of expression of EPHX1, and the results implicated the multiple roles of EPHX1 in various cells ( 41 ). In the current study, an EPHX1 form(s) responsible for 2-AG hydrolysis was not characterized, and this possibility deserves future detailed investigation.…”
Section: Downloaded Frommentioning
confidence: 67%
“…Strong to moderate immunohistochemical EPHX1 protein staining was observed in synovial blood vessels and lining cells (Backman et al 1999). Moreover, it was shown that the topology of EPHX1 on the cell surface (Alves et al 1993) greatly varies between different cell types (Duan et al 2012). …”
Section: Ephx1 Gene Its Variability and Expressionmentioning
confidence: 99%